Innovation in Family Firms: A Holistic Bibliometric Overview of the Research Field - Aparicio, Gloria; Iturralde, Txomin; Sanchez-Famoso, Valeriano (European Journal of Family Business, 2019)
This paper presents a bibliometric analysis of innovation in family firms, focusing on aspects that prior literature review studies did not fully understand or evaluate. It is based on the bibliometric evaluation of 207 scientific articles published from 1994 to 2017 with innovation in family firms (IFF) as the title of the subject, keywords, and abstract. The authors discuss the results from the perspective of performance indicators and co-authorship visualization, giving a holistic bibliometric overview of the research topic. Research on IFF has emerged as an important study area, with an increasingly established position. The field has attracted researchers and has led to the development of a wide body of literature. This study provides a synthesis and organization of existing knowledge on IFF research.